Excision of Giant Retroperitoneal Immature Teratoma with post-operative chylous ascites - Sana Mosbahi; Sahla Sallemi; Nouha Ben Abdejelil; Salma Mani; Sabrine Ben Youssef; Samia Belhassen; Asma Achour; Saida Hidouri; Amina Wardeni; Lassaad Sahnoun; Mongi Mekki; Mohsen Belghith; et al. (Elsevier, 2021)
Introduction: Retroperitoneal cystic immature teratoma (RCIT) is a rare disease. Its diagnosis and management are challenging. Although, the prognosis is relatively favorable, the post-operative morbidity is not rare.We hereby report a case of RCIT in an infant and describe the difficulties in diagnosis and pre-, per- and postoperative treatment. Case presentation: Our patient was a 50-day-old female born at 35 weeks of gestation without prenatal diagnosis. She was admitted for abdominal distension noticed a few days earlier. Physical examination revealed a large abdominal mass located between the right hypochondrium and the left flank. Computerized tomography showed a 10*12*11 cm heterogeneous retroperitoneal mass with fat components and calcification responsible for the compression of the right kidney. Due to the respiratory distress caused by the tumor, we decided to operate the patient urgently prior to the anatomopathological examination result. The surgical procedure consisted in a large resection of the tumor which necessitated the removal of the right kidney. Postoperatively, our patient developed chylous ascites which was managed with total parenteral nutrition and continuous intravenous infusion of Octreotide. The follow up was uneventful with no recurrence so far. Conclusion: RCIT is a clinically rare disease. The mainstay treatment remains the complete surgical resection of the tumor which could be a complicated procedure. Chylous ascites constitute a rare postoperative complication which can be managed safely by parenteral nutrition and continuous intravenous infusion of Octreotide.